Principles of Subject-Based Arabic Curriculum Development: Language Skills Integration and Contextual Relevance - Siregar, Rahmat Sapaat (MANDAILING GLOBAL EDUKASIA, 2025)
This article explains that the design and development of the Arabic curriculum is pragmatic, guided by a subject-based curriculum. The method used is a qualitative descriptive method. This curriculum model, not only academic aspects are the center of attention, but also by paying attention to teaching methodologies, learning settings and measurements that are real-time, integrative, and sustainable. Based on the relevance, continuity, flexibility, and integration of language skills (listening, speaking, reading, and writing), the key principles affirmed in this learning to manage and direct learning experiences create contextual adaptive structural learners. Literary attitudes are also arranged in three levels with beginner, intermediate and advanced competency gradients, each offering development that suits the needs of students. As motivation, cultural insight, and speaking and writing skills, literary texts, both poetry and prose in Arabic are used as authentic materials. Integrated content and language learning approach, learning and skill development and language content simultaneously. A theoretical review and study, this study seeks to develop a curriculum that meets the needs of authentic students, contextual relevance, and communicative goals. These findings support the argument that a curriculum guided by clear and flexible principles provides more effective and holistic Arabic teaching.